Formação dos coletivos de educadores ambientais para sociedades sustentáveis - Barbosa, Aldovano Dantas [UNESP]; Silva, Andrea [UNESP]; Costa, Januário [UNESP]; Oliveira, Vitória [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The formation of the Collective of Environmental Educators joins and makes interacting scientific research activities and direct pedagogical action in the field of environmental education through differentiated training of educators / researchers built from the Complex Thinking and transdisciplinarity. The impossibility of working with bio-socio-cultural diversity employing the Cartesian Newtonian reveals the possibility of deconstruction and (re) ordering the disciplinary system still present in the training of educators / students. Our horizon is to criticism and self-criticism of Environmental Educators Collective with respect to the environment and environmental education. Articulated Collectives are made up of teachers, students and parents of students from state schools in kindergarten, elementary and secondary by members of GEPEA - Kapok. The Collective are seen as learning communities intersect relate to a dialogical movement.

A Formação dos Coletivos de Educadores Ambientais associa-se e faz interagirem atividades de pesquisa científica e de ação pedagógica direta no campo da Educação Ambiental através de formação diferenciada de educadores e pesquisadores construída a partir do Pensamento Complexo e da Transdisciplinaridade. A impossibilidade de trabalhar com diversidades biosócio-cultural empregando o paradigma cartesiano newtoniano revela a possibilidade de desconstrução e de (re)ordenação do sistema disciplinar ainda presente na formação dos educadores/educandos. Nosso horizonte está para a crítica e auto-crítica dos Coletivos de Educadores Ambientais no que tange ao Meio Ambiente e à Educação Ambiental. Os Coletivos articulados são formados por professores, alunos e pais dos alunos das escolas estaduais de ensino infantil, fundamental e médio por integrantes do GEPEA – Sumaúma. Os Coletivos são vistos como comunidades de aprendizagem que entrecruzam relacionam-se num movimento dialógico.
Keywords: Complex thinking; Environmental education; School; Pensamento complexo; Educação ambiental; Escola